Development of a catalytic enantioselective synthesis of the guanacastepene and heptemerone tricyclic core - Harned, Andrew M. (Tetrahedron, 2019)
For nearly two decades, synthetic chemists have been fascinated by the structural complexity and synthetic challenges afforded by the guanacastepene and heptemerone diterpenoids.Numerous synthetic approaches to these compounds have been reported, but to date the application of enantioselective catalysis to this problem has not been realized. Herein we report an enantioselective synthesis of an advanced intermediate corresponding to the tricyclic core common to the guanacastepenes and heptemerones. Highlights of this work include sequential Pd-catalyzed decarboxylative allylic alkylation reactions to generate the two all carbon quaternary stereocenters, the use of ring-closing metathesis to close the A ring in the presence of a distal allyl sidechain, and a region and diastereoselective oxidation of an trienol ether to introduce oxygenation on the A ring.